Anti-Microbial Susceptibility Pattern of Extended Spectrum Beta-Lactamase (ESBL) Producing Klebsiella spp. Isolated from Chevon Marketed in Anand, Gujarat - Prajapati, Binal R.; Parmar, Bhupendra C.; Bhanderi, Bharat B.; Brahmbhatt, Manoj N.; Nayak, Jitendra B.; Chaudhary, Jitendra H. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was intended to isolate extended-spectrum beta-lactamase (ESBL) producing Klebsiella spp. from chevon samples  (n = 150) collected various retail chevon markets in and around Anand (Gujarat) to check their prevalence and evaluate the hygienic  level. The isolates obtained were also subjected to anti-microbial susceptibility testing. According to Clinical and Laboratory Standards  Institute (CLSI) guidelines, Bacterial isolation, identification, and anti-microbial susceptibility tests were performed. Out of 150 samples,  Klebsiella spp. were recovered from 85 chevon samples with an overall prevalence of 56.67%. The highest prevalence was observed in the  intestine (76.67%), while the lowest was observed in muscle samples (36.67%) with intermediate prevalence in other samples like heart,  liver, and water. Amongst Klebsiella spp. isolates, 100 % antibiotic resistance was detected towards ampicillin and ceftazidime, followed  by cefepime (64%) and ceftazidime/clavulinic acid (63%); whereas higher sensitivity was detected towards amoxicillin/clavulanic acid  (89.41%) followed by gentamicin (70.58%) and amikacin (61.17%). The high prevalence of ELBS producing Klebsiella spp. with greater  anti-microbial resistance suggest the judicious use of antibiotics and the need to track and monitor the spread of ESBL producing strains  in food-producing animals to safeguard public health.
Keywords: Antibiotics resistance; Chevon; ESBL; Klebsiella spp; Prevalence